Penyuluhan DAGUSIBU Obat sebagai Upaya Peningkatan Pengetahuan Ibu PKK di Desa Kedungpring, Kemranjen-Banyumas - Dwiki Fitri; Wahyu Septiani , Sinta; Agamasi, Amalia (Lembaga Pengembangan Kinerja Dosen, 2025)
Mistakes in obtaining, using, storing, and disposing of medication (DAGUSIBU) remain a major issue in Indonesia, including in Kedungpring Village, Kemranjen District, Banyumas Regency. This study aims to improve the knowledge of PKK mothers in Kedungpring Village regarding DAGUSIBU practices through interactive counseling. The method used is a community-based empowerment approach, involving active participation of PKK members in the planning, implementation, and evaluation of activities. The results showed a significant improvement in the participants' knowledge and behavior regarding proper medication management, including proper storage and disposal of expired medication. This activity also encouraged the formation of medication health cadre groups at the RT level to continue educating the community. This DAGUSIBU counseling was proven effective in improving medication literacy at the household level and reducing the risk of medication errors.